34.5k views
21 votes
Please solve this and only answer with image

Please solve this and only answer with image-example-1
User FabianCook
by
5.4k points

1 Answer

10 votes


\cot^4 A - \cot^2 A = 1\\\\\cot^4 A = 1 + \cot^2 A\\\\(\cos^4 A)/(\sin^4 A) = 1 + (\cos^2 A)/(\sin^2 A)\\\\(\cos^4 A)/(\sin^4 A) = (\sin^2 A)/(\sin^2 A)+(\cos^2 A)/(\sin^2 A)\\\\(\cos^4 A)/(\sin^4 A) = (\sin^2 A+\cos^2 A)/(\sin^2 A)\\\\(\cos^4 A)/(\sin^4 A) = (1)/(\sin^2 A)\\\\\cos^4 A = (\sin^4 A)/(\sin^2 A)\\\\\cos^4 A = \sin^2 A\\\\

This then means,


\cos^4 A + \cos^2 A = 1\\\\\sin^2 A + \cos^2 A = 1\\\\

which is the pythagorean trig identity. This concludes the proof.

Therefore, if
\cot^4 A - \cot^2 A = 1, then
\cos^4 A + \cos^2 A = 1

User Gabriel Belini
by
5.1k points